TRACE: a multi-tracer analysis of shallow aquifers to improve geothermal potential assessment - Freundt, Florian; Al Najem, Sami; Aeschbach, Werner; Isenbeck-Schröter, Margot; Kober, Bernd; Kraml, Michael; Grobe, Rene; Wenke, Axel (The Mineralogical Magazine and Journal of the Mineralogical Society of Great Britain and Ireland, 2013)
The assessment of geothermal potential for deep - geothermal energy production currently relies on expensive - 3D reflexion seismic methods to identify adequate fault zones - and geometry of the geothermal aquifer. However, this - analysis does not allow the estimation of hydraulic - permeability of active faults nor provides a characterisation of - the chemical properties of the deep aquifer fluid. Both factors - play an important role in optimising siting of fault related - geothermal wells and operation of geothermal power plants. - The TRACE project aims to combine methods from - hydrogeochemistry and isotope hydrology in the analysis of - shallow groundwater to develop a low cost method for deep - geothermal energy exploration. The main goal is to constrain - the interest area with further methods supporting geophysical - exploration methods. The approach introduced in this - contribution includes the measurement and evaluation of a - wide range of natural isotopic and geochemical. To assess the - fault permeability, the groundwater 3He/4He ratio will be - analysed for mantle signatures pointing to deep water - circulation and upward flux [1]. The hydrogeochemical - analysis and transport modeling will be used to characterise - the origin and flow path of the thermal water [2] and to assess - its suitability for industrial scale energy production. - The Upper Rhine Graben was chosen as the project’s - study region, focusing on three different local areas with - preexisting well and 2D/3D seismic data to allow for - comparison and validation of the study results. Preliminary - results from the first sampling campaign show promising data, - indicating an area of increased interest where elevated helium - ratios coincide with characteristic geochemical data, fault - location and a previously known saltwater anomaly.